2016
DOI: 10.1002/jcp.25633
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast Fusion: Time‐Lapse Reveals Involvement of CD47 and Syncytin‐1 at Different Stages of Nuclearity

Abstract: Investigations addressing the molecular keys of osteoclast fusion are primarily based on end‐point analyses. No matter if investigations are performed in vivo or in vitro the impact of a given factor is predominantly analyzed by counting the number of multi‐nucleated cells, the number of nuclei per multinucleated cell or TRAcP activity. But end‐point analyses do not show how the fusion came about. This would not be a problem if fusion of osteoclasts was a random process and occurred by the same molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 37 publications
2
70
0
Order By: Relevance
“…Syn-1 has already been shown to function in osteoclastogenesis. Syn-1 has been reported to promote formation of multinucleated osteoclasts (30,32), with most recent work suggesting that Syn-1 expression facilitates fusion between two multinucleated osteoclasts but not fusion between two mononucleated osteoclast precursors (30). A known ability of Syn-1 to mediate cell fusion (34) substantiated the hypothesis that Syn-1 involvement in osteoclastogenesis is related to its fusogenic activity.…”
Section: Ocps In This Scenario Although Transient Contacts Between mentioning
confidence: 83%
See 2 more Smart Citations
“…Syn-1 has already been shown to function in osteoclastogenesis. Syn-1 has been reported to promote formation of multinucleated osteoclasts (30,32), with most recent work suggesting that Syn-1 expression facilitates fusion between two multinucleated osteoclasts but not fusion between two mononucleated osteoclast precursors (30). A known ability of Syn-1 to mediate cell fusion (34) substantiated the hypothesis that Syn-1 involvement in osteoclastogenesis is related to its fusogenic activity.…”
Section: Ocps In This Scenario Although Transient Contacts Between mentioning
confidence: 83%
“…Many groups have characterized the osteoclastogenesis using in vitro models based on human monocytes (HMs), murine bone marrow cells (BMC), and macrophage-like murine monocytic RAW 264.7 cells ("RAW cells"). Several proteins have been shown to be involved in osteoclastogenesis and suggested to be involved in OCP fusion, including the following: a regulator of immune properties of dendritic cells, dendritic cell-specific transmembrane protein (DC-STAMP) (21,22); osteoclast stimulatory transmembrane protein (OC-STAMP) (23,24); purinergic receptors (25); S100 proteins (26); protein-tyrosine phosphatase PEST (27); adaptor protein Tks5 (28); an intermediateconductance calcium-activated potassium channel (29); and CD47 (30). Recent studies have also demonstrated that formation of multinucleated osteoclasts depends on clathrin-mediated endocytosis (31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, DC-STAMP and OC-STAMP are the only molecules shown to be expressed by OCps and foreignbody giant cells for their cell fusion (38), making their biologic properties of particular interest in the study field of bone biology. Indeed, several other cell surface molecules, such as meltrin-a, CD47, syncytin-1, and E-cadherin, have been described for their roles in OC fusion, but their expression and activities are not restricted to OCps or giant cells (38)(39)(40)(41)(42). For example, knockdown of OC-STAMP resulted in the inhibition of multinucleated OC formation and decreased expression of genes including transcription factor c-Jun, receptors RANK and c-Fms, TRAF6 signaling molecule, and cell-fusion-related molecule meltrin-a (43).…”
Section: Discussionmentioning
confidence: 99%
“…CD47 and its counterreceptor MFR/SIRPa have been shown to be engaged in the fusion of OC as well as macrophage (44)(45)(46). It has been reported that RANKLstimulated OCps induce CD47, which is engaged in cell fusion of small OCs (1,39,44). However, CD47-KO mice demonstrate osteopetrotic bone phenotype (46), indicating that CD47 plays a role in homeostatic bone remodeling; therefore, it is challenging to develop a therapeutic approach for bone lytic diseases by targeting CD47.…”
Section: Discussionmentioning
confidence: 99%